Hubungan Minat Belajar Dengan Hasil Belajar Mata Pelajaran Tata Busana Di Madrasah Aliyah Negeri 2 Padang. - WASTI, SRIANA; rahmiati, rahmiati; izwerni, izwerni (Journal of Home Economics and Tourism, 2013)
Abstract This study aims to reveal the picture of interest in learning, learningoutcomes lesson reveals the relationship of fashion and interest in learning thesubjects learning outcomes fashion at Madrasah Aliyah Negeri 2 Padang. Thisresearch is descriptive quantitative research that look, review and describewhat the subject under study in order to obtain an answer to the question of theproblems studied. The population in this study were grade 2 IPS as 158 people.The technique of determining the sample is simple random sampling with 40people grade 2 IPS. The data of this study consisted of primary data in the formof questionnaires and secondary data from the original value of students(Legar) semester exam results in the school year 2012/2013. The results of theanalysis of the data showed that the variables of interest in student learning dressmaking courses at MAN 2 Padang is in the category quite well. From 40respondents 8 persons (20%) were studied with both categories, while 32people (80%) showed a remedial learning outcomes unfavorable category.Based on data analysis, Interest in learning the subjects learning outcomesdressmaking at Madrasah Aliyah Negeri 2 Padang has a correlation coefficient(rxy) is equal to 0.552 with the direction of a positive (+). That is, the better theinterest in learning (X), the higher the student learning outcomes (Y). T value(4.078)> from t table (1.686), which means there is a significant effect ofinterest on learning outcomes of students studying subjects in fashion MAN 2Padang.Kata Kunci : Minat Belajar, Hasil Belajar, Mata Pelajaran Tata Busana